2011
DOI: 10.1507/endocrj.k11e-018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recovery time from hypoglycemia in patients with insulin overdose

Abstract: UnfortUnately suicidal insulin overdose often occurs in patients with mental illness [1]. Insulin overdose results in prolonged hypoglycemia. Since there is no appropriate marker to estimate the recovery time from hypoglycemia, prolonged hypoglycemia often persists after stopping glucose supplementation. Here we hypothesized that if a huge amount of insulin is injected, the duration of hypoglycemia depends on the dose of insulin rather than the type of insulin, and provide an equation for the correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The onset of hypoglycaemia can be as soon as 1–2 h or be delayed over 18 h after insulin glargine overdose . Duration of action may be prolonged a few days to a week after an overdose and larger doses have been associated with longer duration, but not the type of insulin . This may be due to changed absorption profiles of even short‐acting insulin due to large injection depots.…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
“…The onset of hypoglycaemia can be as soon as 1–2 h or be delayed over 18 h after insulin glargine overdose . Duration of action may be prolonged a few days to a week after an overdose and larger doses have been associated with longer duration, but not the type of insulin . This may be due to changed absorption profiles of even short‐acting insulin due to large injection depots.…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
“…A recent study showed a positive correlation between recovery time from hypoglycaemia and insulin dose . The prolonged half‐life of insulin resulting from overdose is assumed to be caused by delayed absorption of injected insulin from subcutaneous tissue due to local hypo‐circulation resulting from mechanistic pressure, and occupation of insulin receptors by exogenous insulin . In addition, the distinct absorption mechanism of IDeg might have contributed to the long‐lasting hypoglycaemia in the present case.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, the IRI resulting from IDeg injection remained in the blood for ~400 h, highlighting the risk of unexpected long‐lasting hypoglycaemia in similar cases. A recent study showed a positive correlation between recovery time from hypoglycaemia and insulin dose . The prolonged half‐life of insulin resulting from overdose is assumed to be caused by delayed absorption of injected insulin from subcutaneous tissue due to local hypo‐circulation resulting from mechanistic pressure, and occupation of insulin receptors by exogenous insulin .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 39-year-old non-diabetic woman overdosed on 300 units of subcutaneous lispro insulin and required supplemental glucose for more than 11 hours (3), two times longer than would be expected from the usual pharmacodynamics properties (4). Prolonged hypoglycemia could be due to the cumulative effect of insulin or delayed insulin absorption due to local hypo-perfusion from mechanical pressure (5). Theoretically, very high insulin levels may overwhelm receptor-mediated clearance, especially in the liver, which could result in a prolonged half-life.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, authors such as Ohyama et al have suggested that the duration of hypoglycemia may be better estimated by the total dose of insulin rather than the insulin type (5). Based on a review of 33 Japanese cases of subcutaneous insulin overdose that range from 50 units of regular and premixed insulin to 3000 units of NPH insulin, they report a correlation of recovery time in hours from hypoglycemia (y) and insulin units (x) as y = 0.045x (r = 0.88, p < 0.001), and with cases of less than 1500 units of subcutaneous insulin, y = 0.062x (r = 0.88, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%